A Metadata Search Approach to Keyword Query in Relational Databases - Jarunee Saelee; Veera Boonjing (My University, 2013)
This paper proposes an effective approach to keyword query in relational databases.It uses a semantic graph model consisting of database metadata, database values, user terms, and their semantic connections.Keywords of a query determine all possible connected subgraphs of the semantic model.A query answer is a subgraph with the minimum connections.In addition, the approach proposes to rank result tuples of the answer subgraph using the IR-style ranking function.Our experiment results show that queries with metadata terms give more precise answers than queries without them.
Keywords: Advanced Database Systems and Queries